Gilles Deleuze's difference and repetition : a critical introduction and guide - Williams, James, 1965- (Edinburgh University Press, 2013)
A revised, expanded and fully up-to-date critical introduction to Deleuze's most important work of philosophy By critically analysing Deleuze's methods, principles and arguments, James Williams helps readers to engage with the revolutionary core of Deleuze's philosophy and take up positions for or against its most innovative and controversial ideas. New for this edition. A new chapter on questions of method around important concepts such as intensity, anarchic distribution, transcendental illusion and distinctness Reflections on the place of judgement and action in Deleuze's work in order to explain its ethical and political dimensions A new critical section, which guides students through the key debates and oppositions by engaging with latest interpretations of Deleuze by Levi Bryant, Anna Sauvagnargues, Daniel W. Smith, Henry Somers-Hall and Miguel de Beistegui